Relationship Marketing: Tools for Ensuring Return on Equity - Chalise, Dhan Raj (Nepal Journal of Multidisciplinary Research, 2021)
Introduction: Relationship Marketing helps to create the long term relationship between customer and banking institution providing the satisfying experience in banking services. It also helps to drive the banking excellence to the next level. It also helps to relive the banking stigma of beating fellow competitors in similar field. Relationship marketing can provide the positive vibe in the mean time of crisis as contemporary world is in seek of forwarding the feet into peculiar pat of economic growth. Bank in mean time has to create positive financial vibe in society which can be done through fulfillment of corporate social responsibility. Purpose: The main purpose of this research paper is to find out how relationship marketing ensures returns on equity. Design: The researcher wants to prove the points through numeric justification. Researcher has designed self-structured questionnaire for collecting primary data. For making research more centric towards research question researcher has presented his ideas through data. Therefore, researcher has adopted quantitative research design for this research. Findings: Bank conducts its financial activities in society thus bonding between society and bank is inevitable. In this regard, Relationship Marketing provides the path for ensuring equity value. In the research, researcher tested the relationship among several hypotheses through statistical analysis facts. The research reveals significant relationship marketing as major aspect of ensuring returns on equity. Originality/Value: Self designed questionnaire and field survey has make research more native. Besides that, there are limited works carried on in the field of relationship marketing making research precisely unique. To provide more accuracy and ease for understanding, researcher has presented the research works through various well defined statistical chat adding value to research work. Implication: Researcher is convinced that this research work will provide new arena of study for upcoming researcher. Likewise, statistical justifications in research can help policy maker to rigorously understand relationship marketing and create new strategies for equity magnification. Likewise, research is helpful for academician to understand current trend of marketing prevailing around the world.